Kewenangan Pengadaan Tanah Bagi Kepentingan Umum Berdasarkan Undang-Undang Nomor 2 Tahun 2012 : (Suatu Tinjauan Atas Gugatan Pembangunan Jalan Tol Trans Sumatera Ruas Padang - Sicincin) - Saputra, Kadek Wahyudi; Suparji; Rifai, Anis (Jurnal Bedah Hukum, 2024)
In order to actualize the mandate of Pancasila and the 1945 Constitution, that is for justice and prosperity for society, the Indonesian’s Government needs to carry out national development. One of the national developments that carried out by the Indonesian’s Government is through the infrastructure development. The infrastructure’s development that is currently being built by the Indonesian’s Government is the Construction of the Trans Sumatera Toll Road (“JTTS”), which is assigned to PT Hutama Karya (Persero), and its construction requires a land acquisition process. The land acquisition process is often creates problems and obstacles. The purpose of this writing is to find out who is the authorized party to carry out the land acquisition and what is the impact of the delays in the land acquisition process in JTTS development, especially on the Padang – Sicincin Section. The writing method uses in this writing is the doctrinal writing method. From this writing it can be seen that the implementation of the land acquisition for the public interesy is in the authority of the Indonesian’s Government and the constrained land in the acquisition process has resulted in the delays of the JTTS development. Dalam rangka mewujudkan amanat Pancasila dan Undang-Undang Dasar Tahun 1945, yaitu untuk keadilan dan kemakmuran masyarakat, Pemerintah Indonesia, perlu melakukan pembangunan nasional. Pembangunan nasional yang dilakukan Pemerintah salah satunya melalui pembangunan infrastruktur. Pembangunan infrastruktur yang saat ini sedang dibangun oleh Pemerintah adalah Pembangunan Jalan Tol Trans Sumatera (“JTTS”) yang ditugaskan kepada PT Hutama Karya (Persero), dan dalam pembangunannya membutuhkan proses pengadaan tanah. Pengadaan tanah yang dilakukan ini sering kali menimbulkan permasalahan dan kendala. Tujuan penulisan ini adalah untuk mengetahui siapa yang berwenang dalam menyelenggarakan pengadaan tanah dan bagaimana dampak dari terkendalanya proses pengadaan tanah tersebut dalam Pembangunan JTTS, khususnya pada Ruas Padang – Sicincin. Adapun metode penulisaan ini menggunakan metode penulisan doktrinal. Dari penulisan ini dapat diketahui bahwa penyelenggaraan pengadaan tanah untuk kepentingan umum merupakan kewenangan Pemerintah dan proses pengadaan tanah yang terkendala ini mengakibatkan keterlambatan pada Pembangunan JTTS.